Drivers of Ar-Rahnu (pawn) acceptance: Malaysian evidence - Mohd Thas Thaker, Hassanudin *; Ahmad, K.; Mohd Thas Thaker, M. A.; Anwar, A. P.; Chandra Sakaran, K. (Emerald, 2020)
Purpose: The purpose of this paper is to examine the factor persuading the acceptance of Islamic pawn broking (Ar-Rahnu) among Islamic bank customers. Design methodology approach: The authors collected the data using a self-administered questionnaire design and analysed using SPSS Statistics and smart partial least square. The study is restricted to only respondents who are based in the area of Klang Valley (Selangor and Kuala Lumpur), as these two areas have a larger number of Islamic banks and a decent number of Islamic banks’ clients. A total of 381 respondents’ responses are used for this study, and the constructs involved for analysis purpose are affect, social factor, facilitating conditions, perceived financial benefits and perceived risk constructs. Findings: The finding suggests a significant positive association for social factor and perceived risk, while negative association learnt for affect on acceptance of Ar-Rahnu financing. On the same note, the facilitating condition and perceived financial benefit are found insignificantly related. Practical implications: The findings generated from this study are expected to enrich the literature on the body of knowledge, as it has served to broaden the understanding of the Ar-Rahnu acceptance level in Malaysia. As mentioned, there is limited literature available using this type of financing. Existing studies focus too much on conventional financing products such as personal financing, credit card, short-term loan and many others. Less attention is given to Ar-Rahnu financing. Thus, this study expected to add value to the literature available in the context of Islamic pawn broking business. Moreover, the findings of this study will be very helpful for the Islamic financial institutions to find the best way to retain Ar-Rahnu clients and encourage more client to choose Ar-Rahnu as a mode of financing. Originality value: This study owns greater potential to assist Islamic financial institutions to discover the best techniques to retain and encourage the grander number of clients for Ar-Rahnu as a mode of financing.